2017
DOI: 10.1523/jneurosci.2219-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Dendrites of CA2 and CA1 Pyramidal Neurons Differentially Regulate Information Flow in the Cortico-Hippocampal Circuit

Abstract: The impact of a given neuronal pathway depends on the number of synapses it makes with its postsynaptic target, the strength of each individual synapse, and the integrative properties of the postsynaptic dendrites. Here we explore the cellular and synaptic mechanisms responsible for the differential excitatory drive from the entorhinal cortical pathway onto mouse CA2 compared with CA1 pyramidal neurons (PNs). Although both types of neurons receive direct input from entorhinal cortex onto their distal dendrites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 64 publications
14
60
0
Order By: Relevance
“…We previously found that CA2 receives a much greater excitatory drive from PP inputs than does CA1 or CA3 (Chevaleyre and Siegelbaum, 2010; Srinivas et al, 2017; Sun et al, 2014). Here we examined the heterogeneity of direct cortical excitation of CA3 across the transverse axis.…”
Section: Resultsmentioning
confidence: 97%
“…We previously found that CA2 receives a much greater excitatory drive from PP inputs than does CA1 or CA3 (Chevaleyre and Siegelbaum, 2010; Srinivas et al, 2017; Sun et al, 2014). Here we examined the heterogeneity of direct cortical excitation of CA3 across the transverse axis.…”
Section: Resultsmentioning
confidence: 97%
“…As early as 1934, Lorente de Nó observed significant pyramidal cell dendritic heterogeneity in mouse, monkey, and human brain (Lorente de Nó, 1934). More recent studies further describe hippocampal pyramidal neuron subtype morphological and electrophysiological differences based on hippocampal subregion (Ishizuka et al, ; Mercer et al, ; Srinivas et al, ) and within hippocampal subregions (Bartesaghi & Ravasi, ; Li et al, ; Sun et al, ). In this study, we attempted to determine if a heterogeneous population of pyramidal neurons exists in mouse CA2 similar to that in guinea pig, and if so, whether the heterogeneity can result in any consequential physiological properties.…”
Section: Discussionmentioning
confidence: 99%
“…CA2 pyramidal neurons have been shown to receive excitatory input from mossy fibers from the dentate gyrus (DG) and SCs from CA3 that form synapses primarily onto proximal apical dendrites in the stratum radiatum (Lorente de Nó, 1934). CA2 neurons also receive excitatory synaptic input on more distal apical dendrites localized in the SLM from Cajal–Retzius cells originating within the hippocampal formation (Anstotz et al, ; Anstotz, Lee, Neblett, Rune, & Maccaferri, ) as well as outside the hippocampus from hypothalamic SuM (Borhegyi & Leranth, ; Kocsis & Vertes, ; Magloczky et al, ) and EC layer II neurons (Chevaleyre & Siegelbaum, ; Kohara et al, ; Srinivas et al, ). Activation of SC or EC inputs onto CA2 pyramidal neuron apical dendrites via stimulating electrodes placed in either the SR or SLM, respectively, revealed differences in relative effectiveness of synaptic input in Mb‐like cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EC sends exceptionally strong input to CA2. See (Bartesaghi & Gessi, ; Chevaleyre & Siegelbaum, ; Srinivas et al, ; Sun et al, ). (d) Illustration of generalizing spatial representation in EC.…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%